Quasi-static and dynamic tensile properties of fiberglass/epoxy laminate sheet - Chen, Wensu; Meng, Q.; Hao, H.; Cui, J.; Shi, Y. (Elsevier BV, 2017)
Fiberglass/epoxy laminate or structures strengthened by fiberglass/epoxy laminate might be subjected to dynamic loadings such as impact and blast. Understanding the dynamic material properties of the fiberglass/epoxy laminate is important to predict the behavior of fiberglass/epoxy laminate or its strengthened structure against dynamic loading. In this study, unidirectional quasi-static and dynamic tensile tests on fiberglass/epoxy laminate were carried out to investigate its dynamic material properties. The strain rate for quasi-static and low velocity test varied from 2.08E-05 to 1.04E-01 s-1. The high speed dynamic tests were conducted by INSTRON® VHS 160/100-20 machine at the strain rate from 2.75 to 115 s-1. The strain rate effects on the tensile strength, failure strain and Young's Modulus of fiberglass/epoxy laminate were investigated. Based on the testing data, empirical formulae were derived to predict the dynamic enhancement of tensile material properties of fiberglass/epoxy laminate as a function of strain rates, which can be used to model the dynamic material properties in the numerical simulation of structural responses.